Active travel behaviour in the family environment: protocol for the mixed-methods cross-sectional ARRIVE study. Issue 2 (1st February 2022) - Reimers, Anne Kerstin; Marzi, Isabel; Beck, Franziska; Engels, Eliane; Renninger, Denise; Buttazzoni, Adrian; Krieger, Claus; Demetriou, Yolanda
Abstract : Introduction: Active travel is an important source of physical activity and a primary contributor to overall health among adolescents. To understand and promote active travel behaviour in adolescents, developing a more robust understanding of the predictors of active travel and its associated decision-making processes is needed. Situated within a theoretical socioecological framework for adolescent travel behaviour, the mixed-methods Active tRavel behavioR in the famIly enVironmEnt study aims to quantitatively assess the influence of several predictors of adolescent travel behaviour, and to qualitatively understand the associated decision-making processes of both adolescents and parents. Methods and analysis: Our mixed-methods approach will feature online surveys and semistructured interviews. The online questionnaire, developed in accordance with a theoretical framework of adolescent active travel, will examine adolescent travel behaviour with respect to four different destinations while controlling for multiple relevant individual, social and physical environment factors. To enable the comparison of adolescent and parental perspectives, the questionnaire will be answered by a representative sample of German adolescents (11–15 years old) and their parents. Our semistructured interviews, likewise framed based on the central tenets of the theoretical framework of adolescent active travel, will seek to explore the decision-making process of families regarding travel mode choice via conducting interviews with each member (ie, father, mother, adolescent). To investigate travel decision-making processes, adolescents and their parents will be invited to talk about trips they undertook using both active and passive transport modes during the last week. Thematic analyses will be conducted to highlight the central concerns, priorities and values of participants' decision-making processes. Ethics and dissemination: This study has received ethical approval from the ethics commission of the Friedrich-Alexander-University Erlangen-Nuremberg. Study results will be disseminated at scientific conferences and published in peer-reviewed journals. Additionally, study findings will be made publicly available to relevant health, policy, and research stakeholders and groups.